Anfíbios anuros de lagoas da planície de inundação do alto rio Paraná. - Affonso, Igor de Paiva (2012)
This study was conducted in adjacent ponds from three major rivers in the upper Paraná River floodplain in order to verify the influence of connectivity on the spatial variability of anuran assemblages. We sampled three permanently connected ponds and three seasonally connected ponds to rivers Ivinhema, Bahia and Paraná, where transects were done through 1 hour transects to identify and count amphibians in calling activity. We used a multivariate method of beta diversity to test the spatial variability of the assemblages of amphibians. Were found 24 species distributed in five families: Bufonidae (1); Hylidae (13); Leuiperidae (3); Leptodactylidae (6) and Microhylidae (1). There was a difference in species richness and abundance both between lakes with and without connection with rivers and among the river systems. The difference between the spatial variability of assemblages was significant, so that lakes permanently connected with the rivers have greater variability in relation to seasonally connected lagoons. Thus, this study suggests that the connectivity of the lakes with the rivers appears to be a characteristic that influences the occurrence of amphibians.